2019
DOI: 10.1063/1.5116898
|View full text |Cite
|
Sign up to set email alerts
|

Lasing without population inversion in N2+

Abstract: We experimentally demonstrate the existence of long-lived coherent polarizations coupling simultaneously ground state X (X2Σg+) to excited states A (A2Πu) and B (B2Σu+) of N2+ inside a plasma created by a short intense laser pulse at 800 nm. This three-level V-scheme arrangement is responsible for a strong optical gain without population inversion at the B–X transition at 391.4 nm. Simulations based on Maxwell-Bloch equations reproduce well the kinetics and the pressure dependence of the gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 30 publications
7
42
0
1
Order By: Relevance
“…In the N2+ lasing, the quantum coherence not only brings strong nonlinear effects, but also leads to the superradiant emission and also the coherent control, which have been observed with N2+ ions.…”
Section: Molecular Nitrogen Ion Lasingmentioning
confidence: 95%
See 3 more Smart Citations
“…In the N2+ lasing, the quantum coherence not only brings strong nonlinear effects, but also leads to the superradiant emission and also the coherent control, which have been observed with N2+ ions.…”
Section: Molecular Nitrogen Ion Lasingmentioning
confidence: 95%
“…In contrast, we found that the fluorescence signal at 391.4 nm does not show any significant change for the time delay tuning. It indicates that the population density in the B2normalΣu+ state is not changed in the presence of the weak 800 nm control pulse …”
Section: Molecular Nitrogen Ion Lasingmentioning
confidence: 97%
See 2 more Smart Citations
“…In the recent work of Ref. [35], a different lasing without an inversion mechanism has been proposed to cause the gain at the 391 nm line based on the existence of long-lived coherent polarizations coupling simultaneously the states X , B, and the intermediate first excited electronic state A in N + 2 . The present amplification scheme relies on rotational dynamics and does not require coherences between the electronic states of the ion, even though such coherence is inevitably created by the pump pulse driving the molecular ion after ionization of the neutral.…”
Section: Introductionmentioning
confidence: 99%